Irrigation Effects on Volatile Profile and Essential Oil Yield of Guayule During Flowering - Emilio José González-Navarro; Maria de las Mercedes García-Martínez; María Engracia Carrión Jiménez; Manuel Carmona; Amaya Zalacain (Agriculture)
Guayule (Parthenium argentatum A. Gray) has the potential to be an alternative source of rubber if its co-products can be exploited on an industrial scale. Among the co-products that have garnered interest are the essential oils (EOs), which can reach relatively high yields. In the present study, the production and profile of EOs from two guayule accessions, AZ-3 and AZ-5, across different flowering stages (5 months) were analyzed under two irrigation regimes (100% and 50% of crop water evapotranspiration) and compared with control plants that received no additional water, (considered as a water-stress condition). The results showed that the extracted EO yield was consistently higher in the AZ-3 accession than in the AZ-5, especially under water-stress conditions, and that the flowering stage significantly affected the yield irrespective of the accession. Furthermore, differences in EO composition were observed between accessions, with AZ-3 containing more monoterpenes and AZ-5 containing more sesquiterpenes. The yields obtained underline the economic potential of guayule EO production, especially under water-stress and flowering conditions, and position it favorably against other aromatic plants. These results provide valuable insights for optimizing guayule cultivation to increase EO yields, with both economic and environmental benefits.